The role of resection for melanoma metastases to the pancreas. Issue 12 (December 2022) - Guerra, Francesco; Coletta, Diego; Deutsch, Gary B.; Giuliani, Giuseppe; Patriti, Alberto; Fischer, Trevan D.; Coratti, Andrea; ,; Serafini, Simone; Surjan, Rodrigo; Milanetto, Anna C.; Campra, Donata
Abstract: Background: Among patients with distant metastatic melanoma, the site of metastases is the most significant predictor of survival and visceral-nonpulmonary metastases hold the highest risk of poor outcomes. However, studies demonstrate that a significant percentage of patients may be considered candidates for resection with improved survival over nonsurgical therapeutic modalities. We aimed at analyzing the results of resection in patients with melanoma metastasis to the pancreas by assessing the available evidence. Methods: The PubMed/MEDLINE, WoS, and Embase electronic databases were systematically searched for articles reporting on the surgical treatment of pancreatic metastases from melanoma. Relevant data from included studies were assessed and analyzed. Overall survival was the primary endpoint of interest. Surgical details and oncological outcomes were also appraised. Results: A total of 109 patients treated surgically for pancreatic metastases were included across 72 articles and considered for data extraction. Overall, patients had a mean age of 51.8 years at diagnosis of pancreatic disease. The cumulative survival was 71%, 38%, and 26% at 1, 3 and 5 years after pancreatectomy, with an estimated median survival of 24 months. Incomplete resection and concomitant extrapancreatic metastasis were the only factors which significantly affected survival. Patients in whom the pancreas was the only metastatic site who received curative resection exhibited significantly longer survival, with a 1-year, 3-year, and 5-year survival rates of 76%, 43%, and 41%, respectively. Conclusion: Within the limitations of a review of non-randomized reports, curative surgical resection confers a survival benefit in carefully selected patients with pancreatic dissemination of melanoma. Graphical abstract: Image 1